Results analysis of the regional research competition for secondary school students using information and communications technology - Zulfiya F. Kamaldinova; Nadezda V. Kulikova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with specific issues relating to the implementation of one of the priority directions of state policy of Russia is to work with gifted young people. The highly structured system of activities helped identify and develop gifted young people in science, engineering and technology and innovation development of the Samara region and allowed to define tasks and directions of the contests of students research projects in the competition "Vzlet".The article analyzes the results of the regional research competition held for the past 3 years in the Samara region for gifted secondary school students. The key quantitative indicators which may lead to further qualitative analysis were presented, specifically, the total number of participants, the number of submitted projects in different research areas, project advisors, participating educational organizations, and winning projects. In addition, the rates of those who started the competition and those who successfully completed it were analyzed. The articles offers conclusions and discusses future directions for the competition.